Psychological functioning, coping styles and their relationship to appraisal of physical limitations following invasive surgical procedures for soft‐tissue sarcoma: A qualitative study. Issue 8 (27th March 2020) - Košir, Urška; Denis‐Larocque, Gabrielle; Tsimicalis, Argerie; Freeman, Carolyn; Turcotte, Robert E.; Cury, Fabio; Alcindor, Thierry; Goulding, Krista
Abstract: Background and Objectives: This study explored psychological functioning and coping styles in adult patients with soft‐tissue sarcoma who underwent surgical procedures in a single expert sarcoma medical center in Canada. Methods: This is a qualitative study with three formats of data collection. The interview guide was based on theoretical health‐related quality of life model. We began the investigation with 2 online and 2 in‐person focus groups. Four individual semistructured interviews were added to further explore emerging themes. Data were analyzed using inductive thematic networks approach. Results: Twenty‐eight adults (13 female, 24‐75 years of age) participated. In the domain of psychological functioning we identified three main themes; changes in mood, worry, and body image concerns. In the domain of coping styles, we identified four adaptive coping styles; positive reframing and optimism, finding a purpose, being proactive, and using humor. Among the maladaptive coping styles, we found passive acceptance, and avoidance and denial. Conclusions: Psychological well‐being can be contingent on physical functioning and coping styles in adults with soft‐tissue sarcoma. Both psychological and physical function impact quality of life. Patients with more physical limitations, psychological distress and maladaptive coping styles should be monitored for their well‐being.